Ecriture-reportage et vision impressionniste dans Vers Ispahan, de Pierre Loti .......... 9 - Anghel, Liliana (Pensées orientale et occidentale : influences et complémentarité II, 2021)
REPORT-WRITING AND IMPRESSIONISTIC VISION IN PIERRE LOTI’S TOWARDS ISFAHANThis article emphasizes Pierre Loti’s manner of revealing, in the beginning of the 20th century, to the European readers, an unknown country. The text emphasizes Pierre Loti’s manner of revealing an unknown country to European readers at the beginning of the 20th century. It is Peris, so distant on geographic and cultural level. Loti’s book, Towards Isfahan, proves both his skill in report writing and his painting talent as he creates unforgettable descriptions following his truly impressionist sensibility.